On The Representations and Characters of Quaternions Group Q8 (European Journal of Pure and Applied Mathematics, 2024)
We are interested in studying the linear representations of the Quaternions group Q8 by determining it’s charater table and irreducible representations which allows us to construct some representations of degre 6 and 8 of Q8.
Keywords: Irreducible representation; Character table; Quaternions group; Group Q8